Latest Progress and Future Trends of Technologies Used by RAN for 3GPP 5G NTN - ZHANG Lu; WANG Xue; MANG Ge; WANG Gaojian; ZHANG Shaowei; ZHONG Hua; ZHANG Yang; ZHU Xuetian (天地一体化信息网络)
Among multiple technical routes qualified for building satellite networks, the route which is based on 3GPP 5G NTN and its evolution has its own unique advantages, including fully reusing the mature industry chains of network equipment and terminal for terrestrial networks, dramatically reducing the difficulty and cost of the development and deployment for space segment, and enabling the smooth and continuous evolution toward the future 6G systems. Focused on RAN for 3GPP 5G NTN, after briefly reviewed the key contents of the first version of 5G NTN standard introduced in 3GPP Rel-17,this paper firstly summarized the technical progress in 3GPP Rel-18 which had been officially published in 2024 June, then introduced the technical topics in 3GPP Rel-19 which had started the formal discussions recently, and finally looked into the technology trends in future 3GPP Rel-20+.